Analysis of Environmental Management Policies, Livestock Husbandry Practices, and Production Technology on Cattle Farm Productivity in West Java - Sahala, Josua; Pahrijal, Rival; Arini, Rani Eka (West Science Interdisciplinary Studies, 2024)
This research explores the effects of environmental management policies, livestock husbandry practices, and the adoption of production technologies on the productivity of cattle farms in West Java, Indonesia. Using a combination of quantitative and qualitative methodologies, data were collected from 100 cattle farms across three productivity levels. Statistical analysis, including multiple regression, was employed to assess the influence of these factors on farm productivity. The results indicate that the adoption of production technologies had the most significant positive impact on productivity, followed by adherence to environmental management policies and the implementation of advanced husbandry practices. Qualitative findings support the quantitative results, highlighting the role of governmental support and training in facilitating the adoption of effective farming practices. This study underscores the necessity of integrated approaches that enhance both sustainability and efficiency, recommending policies that support technological innovation and environmental compliance. The findings serve as a valuable reference for policymakers and farm managers aiming to optimize productivity and sustainability in livestock farming.